Land administration for housing production: analysis of need for interagency integration. Issue 334 (January 2014) - Agunbiade, M. E.; Rajabifard, A.; Bennett, R.
<x content-type="archive" xml:space="preserve">Abstract</x> In most country contexts the activities of government land administration agencies, those dealing with the functions of land tenure, valuation, planning, and development, are disparate and lack harmonisation. This paper analyses the imperative for integrating these functions across and between government structures. An exploratory approach synthesising existing research and newly acquired empirical case study data from Victoria-Australia, and Lagos-Nigeria underpins the discussion. Drivers for interagency integration are exposed and discussed including: cost inefficiencies for actors in the development process, the effectiveness of planning enforcement, and redundancy in land information. Opportunities for integration are revealed through analysis of the land development process, land information infrastructures, and urban management policy.